Aglomeraç\~oes acadêmicas relevantes na nova configuraç\~ao espacial do ensino superior brasileiro - Danilo Jorge Vieira; Fernando Cezar de Macedo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The country's higher education system assumed a new geographical configuration in the twenty-first century, under the impulse of two simultaneous processes of growth and reagglomeration, both characterized by a spatially less concentrated pattern. Thus, in addition to an evolution that has managed to attenuate the pre-existing asymmetries, it is possible to observe, at the same time, the constitution of new centers of polarization of the system, with the increasing density of its activities in more diverse areas of the national territory. This study examines such transformations based on the concept of Relevant Academic Agglomeration (RAA), elaborated with the purpose of identifying those Immediate Geographic Regions whose degree of concentration of undergraduate and graduate activities has been transformed into specialized centers of higher education.
Keywords: I23; I25; R58; 330; higher education institutions; regional development; regional policy